2014
DOI: 10.1007/s10792-014-9955-3
|View full text |Cite
|
Sign up to set email alerts
|

Ex-PRESS outcomes using mitomycin-C, Ologen alone, Ologen with 5-fluorouracil

Abstract: To compare the complication rate and effectiveness of mitomycin C (MMC), Ologen alone, and Ologen with 5-fluorouracil (5-FU) as adjunctives with Ex-PRESS mini shunt for medically uncontrolled glaucoma. Retrospective comparative study of 59 Ex-PRESS mini shunt trabeculectomy operations coupled with Ologen implantation alone, transient MMC application or Ologen implantation with 5-FU as adjunctive treatment. Eight eyes (7 patients) received Ologen alone, 37 eyes (34 patients) received MMC, and 14 eyes (14 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A small retrospective comparative case series of eyes that underwent trabeculectomy combined with the ExPress shunt showed that eyes in which the Ologen CM was used alone had worse IOP outcomes, a higher reoperation rate, and a higher rate of bleb leaks compared to eyes that underwent trabeculectomy with Ologen CM with adjunctive 5-FU or eyes that underwent trabeculectomy with MMC alone [21]. The investigators used the 6- × 2-mm CM implant in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A small retrospective comparative case series of eyes that underwent trabeculectomy combined with the ExPress shunt showed that eyes in which the Ologen CM was used alone had worse IOP outcomes, a higher reoperation rate, and a higher rate of bleb leaks compared to eyes that underwent trabeculectomy with Ologen CM with adjunctive 5-FU or eyes that underwent trabeculectomy with MMC alone [21]. The investigators used the 6- × 2-mm CM implant in this study.…”
Section: Discussionmentioning
confidence: 99%